Discrimination in grading? Experimental evidence from primary school - Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper studies the effect of teacher expectations on essay grades in an experimental setting. To this purpose, we randomly assign Turkish or German first names to a set of essays so that some teachers believe a given essay was written by a German native pupil, whereas others believe it was written by a pupil of Turkish origin. We find that essays obtain significantly lower grades and lower secondary school recommendations when bearing a Turkish sounding name.
Keywords: I20; 330; Experiment; discrimination; grading; pupils with migration; background; Schüler; Ethnische Diskriminierung; Lehrkräfte; Bildungsabschluss; Türken; Deutsche; Deutschland